2016
DOI: 10.1128/jvi.02974-15
|View full text |Cite
|
Sign up to set email alerts
|

The 1918 Influenza Virus PB2 Protein Enhances Virulence through the Disruption of Inflammatory and Wnt-Mediated Signaling in Mice

Abstract: The 1918 A nnual influenza epidemics cause significant morbidity and mortality. On occasion, novel influenza A strains emerge that are capable of producing severe respiratory disease on a global scale (1). The 1918-1919 pandemic was an unprecedented event, with an estimated 40 to 50 million deaths worldwide (2, 3). Sequence analysis indicates that the 1918 pandemic influenza virus is avian in origin (4-8) and 1918 viral genes are highly homologous to those of circulating avian influenza H1N1 viruses (9). In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 71 publications
0
29
0
Order By: Relevance
“…All infected samples were confirmed to express viral M2 mRNA by quantitative RT-PCR (Forero et al, 2015; McCown and Pekosz, 2005). Individual cRNA samples were then hybridized to oligonucleotide microarrays for gene expression profiling using SurePrint G3 Human Gene Expression v2 Microarray Kit (G4851A; Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…All infected samples were confirmed to express viral M2 mRNA by quantitative RT-PCR (Forero et al, 2015; McCown and Pekosz, 2005). Individual cRNA samples were then hybridized to oligonucleotide microarrays for gene expression profiling using SurePrint G3 Human Gene Expression v2 Microarray Kit (G4851A; Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…In a very recent study, the 1918 influenza virus PB2 protein was shown to be a virulence factor interfering with inflammatory and Wnt-mediated signaling in mice. Both, beta-catenin-dependent and -independent Wnt signaling pathways were repressed and associated with impaired lung regeneration and repair (139). Taken together, this illustrates that depending on the infection mechanism and the infected host cell, pathogens may exploit the Wnt signaling machinery in a very specific manner.…”
Section: Pathogens Exploiting Wnt Signalingmentioning
confidence: 99%
“…S4a). Interestingly, the BM18 influenza PB2 subunit has been linked to the enhancement of both the kinetics and the magnitude of the host response to viral infection, leading to the induction of strong inflammatory responses with increased cellular infiltration in the lungs of infected mice 24 . To identify PB2 amino acid residues involved in the formation of mvRNAs, we aligned the BM18, WSN, NT60 and FJ02 PB2 sequences and found four amino acid positions that distinguish the BM18 and FJ02 polymerases from the WSN and NT60 polymerases: 9 (D→N), 64 (M→T), 81 (T→M), and 661 (A→T) (Fig.…”
mentioning
confidence: 99%